PENGGUNAAN PERMAINAN ULAR TANGGA SEBAGAI MEDIA CHEMO-EDUTAINMENT UNTUK MENCAPAI KETUNTASAN BELAJAR PESERTA DIDIK PADA SUB POKOK BAHASAN SISTEM PERIODIK UNSUR DI KELAS X SMA NEGERI 2 TANAH PUTIH - Sufyanto '; Roza Linda Linda; Herdini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Research on the use of snakes and ladders game as chemo-edutainment media has been done to achieved mastery of students on the subject periodic system of element in class X SMA Negeri 2 Tanah Putih. Form of the research is pre-experiment research with one-shot study case design. Retrieval of data started from August 27 to September 24, 2014. Sample of research is class X MIA 2. Data analysis technique used to calculate presentage of competency mastery of knowledge, competency mastery of attitude and competency mastery of skills. Based on the final results obtainable competency mastery of knowledge is 87,87%, competency mastery of attitude is 100% and competency mastery of skills is 100%, it’s means that the application of using snakes and ladders games as chemo-edutainment media can achieve mastery of students on the subject of periodic system of element in class X SMA Negeri 2 Tanah Putih. Keywords           : Snakes and Ladders Game as Chemo-Edutainment Media, Mastery Learning, Periodic System of Element